A comparison between three surface type data sets adopted by the community radiative transfer model. Issue 8 (3rd August 2017) - Zhuge, X.; Zou, X.; Wang, Y.
ABSTRACT: The accuracy of simulated radiances for surface-sensitive visible and infrared channels is affected by the specification of surface type. The current version of Community Radiative Transfer Model (CRTM) employs three surface type data sets, which are referred to as the National Polar-orbiting Operational Environmental Satellite System (NPOESS), the U. S. Geological Survey (USGS), and the International Geosphere-Biosphere Programme (IGBP) data sets, respectively. In this study, the consistencies and discrepancies among these three surface type data sets are examined. The surface type is specified consistently among the three data sets in equatorial and polar regions, but not in other regions especially around 60° N. The desert and snow types have the highest consistency among the three surface type data sets. The tundra in the IGBP data set, the needle-leaf forecast and mixed forest in the NPOESS data set, and the mixed forest in the USGS data set have the greatest discrepancy from the other two data sets. Finally, a canonical case is used to demonstrate that the impacts of the three surface type datasets on CRTM simulations are significant, pointing to a need for a rigorously defined surface type data set.